(untitled) (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2025)
This article explores how the poetic language tradition established by Abai was continued and conceptually transformed in the works of Shakarim. The study focuses on the linguistic, compositional-stylistic, and aesthetic features of their poetry. Descriptive analysis, comparative method, linguopoetic examination, and semantic modeling were employed to investigate the stylistic and semantic transformation of linguistic units within the poetic text. The findings demonstrate that Shakarim not only preserved but creatively expanded Abai’s linguistic tradition. He reinterpreted folk imagery, enriched established expressions with new semantic nuances, and employed alliteration, assonance, anaphora, and epiphora with strong stylistic intent. Shakarim also broadened the expressive capacity of the poetic language through innovative metaphoric constructions, syncretic word combinations, and the personification of abstract concepts. His poetic language reflects a deep connection between aesthetic expression and moral-philosophical worldview, forming a distinctive idiostyle. This study clarifies the continuity and innovation within Kazakh poetic tradition, identifies the aesthetic significance of Abai’s school, and contributes to the theoretical development of linguopoetic analysis. The results offer valuable insights for further research on poetic semantics, linguistic personality, and the evolution of literary style.